Pengaruh TIK dalam Meningkatkan Pembangunan Manusia di Indonesia - Riza, Andika Ahmad; Nelonda, Selli; Anshari, Muhammad (Universitas Negeri Padang, 2025)
Improving human resource quality is one of the strategic priorities within Indonesia’s national development framework. Although the Human Development Index (HDI) shows an upward trend, its growth rate has tended to decelerate over time. This study aims to analyze the impact of the Information and Communication Technology Development Index (ICT Development Index) and ICT skills on human development in Indonesia. The analysis utilizes panel data from 34 provinces over the 2015–2023 period using a fixed effects model. The estimation results show that all independent variables have a statistically significant influence on the improvement of HDI. These findings indicate that technological progress and digital skills play a vital role in enhancing the quality of life. Therefore, policy formulation is needed to promote equitable access to information technology and the enhancement of digital capabilities as the foundation for inclusive and sustainable human development.